Establishment of the first shariah compliant human milk bank: The IIUM Experience in Developing Halimatussadia Mother’s Milk Centre - Jamani, Nurjasmine Aida; Ismail, Hamizah; Syed Abd Hamid, Syed Abdul Khaliq; Barnett, Debbie (2022)
Human milk has been recommended as the best and gold standard in infant feeding in terms of nutritional and immunological value including donor human milk. Donor human milk has gained demand in the recent years when mother own’s milk is not available. There has been an increasing number of human milk banks around the world especially in Southeast Asia. This is to aid in donor milk collection, processing and distribution of a safe donor human milk. In contrast to this development, Muslim countries are still in debate in developing a shariah compliant human milk bank in view of concerns from Fiqh perspectives especially in milk kindship. We present the key issues hindering progress of human milk banking in Malaysia including the quality and safety, issues around regulation and ethical concerns about its establishment. We also highlight the journey and challenges faced in developing and establishing our Halimatussaadia Mother’s Milk Centre.